2015
DOI: 10.4314/ahs.v15i3.10
|View full text |Cite
|
Sign up to set email alerts
|

Occupational skin diseases and prevention among sanitation workers in China

Abstract: Background: Little research has been focused on the health status or the occupational protection awareness of sanitation workers. The policy recommendations on the occupational safety and health of sanitation workers based on the scientific research are also insufficient in developing countries like China. Objective: To study the incidence of dermatoses and the relevance with occupational exposure, protection awareness and protective measures among sanitation workers for better management and protection of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The proportion of common health problems suffered is depicted in table 2. 12 The present study reported 96% suffering from one or more of the common health problems; the most common health problem involved the respiratory system, i.e., cough and/or difficulty breathing (87%) followed by sharp object injury during work hours (71%), gastrointestinal disturbance, i.e., diarrhea and/or dysentery with or without fever (45%), skin conditions like allergy/eczema (34%) and eye problems like watering of eyes/itching/burning sensation in the eyes (27%). Similar findings were reported by Yogesh D Sabde et al and Prabhakumari Chellamma et al…”
Section: Resultsmentioning
confidence: 99%
“…The proportion of common health problems suffered is depicted in table 2. 12 The present study reported 96% suffering from one or more of the common health problems; the most common health problem involved the respiratory system, i.e., cough and/or difficulty breathing (87%) followed by sharp object injury during work hours (71%), gastrointestinal disturbance, i.e., diarrhea and/or dysentery with or without fever (45%), skin conditions like allergy/eczema (34%) and eye problems like watering of eyes/itching/burning sensation in the eyes (27%). Similar findings were reported by Yogesh D Sabde et al and Prabhakumari Chellamma et al…”
Section: Resultsmentioning
confidence: 99%
“…Excessive exposure to UV radiation can result in chronic harmful effects on the skin, eye and immune system (Young and Walker, 2005). Besides skin photo aging caused mainly by UV exposure, many other skin manifestations can be connected with their long periods of standing and heavy manual work which led to varicosity (Yan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The female HCWs likelihood of reporting skin symptoms more than the male HCWs have been attributed to their disproportionately higher exposures to nonoccupational triggers (Meding, 2000). Prejob personal history of skin disease as a major indicator of OSD was reported in China, where sanitation workers had a significantly higher occurrence of OSD compared with administrative staff (Yan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings of higher prevalence of OSD among HCWs than non-HCWs were also reported in the United States, with female HCWs being more affected (Kadivar & Belsito, 2015). Personal history of SDS was also found to aggravate OSDs (Yan, Wang, Wu, & Xu, 2015).…”
Section: Introductionmentioning
confidence: 99%